A morphable ionic electrode based on thermogel for non-invasive hairy plant electrophysiology - Luo, Yifei (2021)
Plant electrophysiology lays the foundation for smart plant interrogation and intervention. However, plant trichomes with hair-like morphologies present topographical features that challenge stable and high-fidelity non-invasive electrophysiology, due to the inadequate dynamic shape adaptability of conventional electrodes. Here, this issue is overcome using a morphable ionic electrode based on a thermogel, which gradually transforms from a viscous liquid to a viscoelastic gel. This transformation enables the morphable electrode to lock into the abrupt hairy surface irregularities and establish a conformal and adhesive interface. It achieves down to one tenth of the impedance and 4-5 times the adhesive strengths of conventional hydrogel electrodes on hairy leaves. As a result of the improved electrical and mechanical robustness, the morphable electrode can record more than one order of magnitude higher signal-to-noise ratio on hairy plants and maintains high-fidelity recording despite plant movements, achieving superior performance to conventional hydrogel electrodes. The reported morphable electrode is a promising tool for hairy plant electrophysiology and may be applied to diversely textured plants for advanced sensing and modulation.